2019
DOI: 10.1016/j.trsl.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Partial remission and early stages of pediatric type 1 diabetes display immunoregulatory changes. A pilot study

Abstract: Type 1 diabetes (T1D) is a chronic metabolic disease of unknown etiology that results from b-cell destruction. The onset of the disease, which arises after a long asymptomatic period of autoimmune attack, may be followed by a relapsing and remitting progression, a phenomenon that is most evident during the partial remission phase (PR). This stage lasts for a few months, shows minor requirements of exogenous insulin and could be explained by a recovery of immunological tolerance. This study aims to identify new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 28 publications
3
16
2
Order By: Relevance
“…All mice with more than 10% of human/murine CD45 chimerism at day 13 were injected either with PBS (n = 3) or the combined therapy (n = 7). Then, a blood sample (50 µl) was obtained at each checkpoint and stained as previously described 23 . The percentage and count of memory regulatory T cells (mTregs, CD3 + CD4 + CD127 low CD25 + CCR4 + CD45RO + ) were analysed weekly throughout the treatment, and total T lymphocyte subsets were analysed at endpoint by flow cytometry from peripheral blood samples.…”
Section: Methodsmentioning
confidence: 99%
“…All mice with more than 10% of human/murine CD45 chimerism at day 13 were injected either with PBS (n = 3) or the combined therapy (n = 7). Then, a blood sample (50 µl) was obtained at each checkpoint and stained as previously described 23 . The percentage and count of memory regulatory T cells (mTregs, CD3 + CD4 + CD127 low CD25 + CCR4 + CD45RO + ) were analysed weekly throughout the treatment, and total T lymphocyte subsets were analysed at endpoint by flow cytometry from peripheral blood samples.…”
Section: Methodsmentioning
confidence: 99%
“…A study in 2018 also found that the remission phase was accompanied by dynamic changes in Treg cells, Th1 and Tc1-cell subsets (13), with the decreased number of Treg cells and increased Th1 and Tc1 cells at the end of the remission phase. A recent study that examined a variety of immune cell subsets and cellular molecules in newly diagnosed children with T1DM found that the level of memory-regulatory T cells (mTreg) decreased after the appearance of clinical symptoms and aTreg and Th17 cells were significantly elevated in the first year of onset (the remission phase often occur) (15). The mTregs were also noted to be positively correlated with C-peptide in T1DM patients (16).…”
Section: Immune Cellsmentioning
confidence: 99%
“…A study showed that the frequency changes of marginal zone B cells (MZB), follicular B cells (FoB), and other B-cell subsets were associated with T1DM, and the regulatory B cells (Breg) have immunomodulatory effects (30). Limited reports showed that the remission phase was accompanied by changes in B-cell frequency (13, 15). Glucose metabolism had also been shown to play an important role in the normal functioning of B cells.…”
Section: Immune Cellsmentioning
confidence: 99%
See 2 more Smart Citations